Creation of a Different Landscape for Cardiovascular Diseases and Diabetes in Europe Through JACARDI Joint Action - Zaletel Jelka; Farkaš Lainščak Jerneja (Sciendo, 2024)
The Joint Action on CARdiovascular diseases and DIabetes (JACARDI) aims to reduce the burden of cardiovascular disease and diabetes in European countries, both at the individual and societal levels. The initiative covers the entire patient journey, from improving health literacy and awareness of cardiovascular diseases and diabetes, travelling through primary prevention among high-risk populations and screenings, reaching people living with cardiovascular diseases and diabetes, improving service pathways, self-management, and labour participation. The project involves 21 European countries, 76 partners and plans to implement 142 pilot interventions, ensuring diversity in terms of cultural backgrounds, public health priorities, and healthcare systems.